Interpretasi Data Geolistrik untuk Memetakan Potensi Air Tanah dalam Menunjang Pengembangan Data Hidrogeologi di Kabupaten Jombang, Jawa Timur: Serli Birlina H, Darsono, Budi Legowo - Serli Birlina H, Serli Birlina H; Darsono, Darsono; Budi Legowo, Budi Legowo (Jurnal Fisika dan Aplikasinya, 2025)
Have done mapping of groundwater potential in supporting the development of data hydrogeology in Jombang, East Java using geoelectric resistivity soundings. Resistivity data acquisition using Schulmberger electrode configuration. Data processing and interpretation of data using Progress Version 3 software and mapping using Surfer software. The results of processing the four districts that rock layers are composed of clay with a value of resistivity 6-10 Om, sandy loam 11-19 Om, sand and sand lempungan 20-90 Om, and sand kerakalan 90-130 Om. Aquifer is believed to be the constituent layers of sand and sand lempungan. The result shows mapping shows areas that have a large potential source of ground water contained in the district Mojowarno. Potential areas of medium groundwater resources in the district Bareng and Mojowarno.